(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2026)
The review examines Insurgentes, misioneras y políticas (2022) by Anabella Gorza, a work derived from her doctoral dissertation (2017), which analyzes women’s participation in the Peronist Resistance between 1955 and 1966 from a gender perspective. Drawing on feminist historiography, the book challenges interpretations that have reduced women’s involvement to a subsidiary role, instead highlighting the density, heterogeneity, and specificity of their political practices. Through the analysis of written and oral sources, the author reconstructs trajectories shaped by tensions between militancy and everyday life, as well as by gender norms that both constrained and enabled women’s political action. Within this framework, the book problematizes the association between Resistance and violence and examines key arenas such as party organization, women’s networks, and political press. The review underscores the book’s central contribution in restoring women as historical subjects and in complicating the analytical categories through which the relationship between gender and politics has been understood. It also points to the potential for further research on the articulation between gender and class.